Implementation of Realistic Mathematic Education (RME) Model to Improve Learning Outcomes in Polyhedron - Hozaima; Agus Subaidi (Indonesian Journal of Mathematics and Natural Science Education, 2023)
This research aims to improve the activity and learning outcomes of class VIII students at Islamic Junior High School Nasy-Atul Muta'allimin Candi. Researchers used the observation method to determine student activity, questionnaires to determine student responses to the Realistic Mathematics Education (RME) learning model, and tests to determine student learning outcomes improvement. The results of data analysis, it can be concluded that student activity from cycle I to cycle II experienced an increase of 0.23. Where in the first cycle an average of 3.01 was obtained and in the second cycle an average of 3.24 was obtained in the good category. Based on the student response questionnaire, it also increased from cycle I to cycle II by 25%, the percentage of students who answered "Yes". Where in the first cycle a percentage of 60.71% was obtained and in the second cycle a percentage of 85.71% was obtained, which indicated that the student's response was positive. Then based on the test results, it also showed an increase of 20%, where in cycle I obtained a percentage of 60% and in cycle II obtained a percentage of 80%. The improvement in test results in cycle II was said to be classically complete because the percentage obtained was ≥75%. So it can be concluded that the use of the Realistic Mathematics Education (RME) learning model can improve student learning outcomes at MTs Nasy-Atul Muta'allimin Candi.